Efficacy of ginger tea and cinnamon tea on primary dysmenorrhea among young adults: A comparative study - Swathi S; Ranjini Murthy P; Shravya CN; Vinaya Kumar T; Prajwal HM; Balakrishna Ragavendrasamy; Lakshmeesha; Nitesh MK; Vineetha AN; Amshuman R Yadav (Indian Journal of Integrative Medicine, 2024)
Background and Objectives: Primary dysmenorrhea affects many women and causes physical and mental suffering. The main cause is the release of prostaglandins, which causes uterine contractions and reduced blood supply. The main objective of the study was to compare the efficacy of ginger tea and cinnamon tea in alleviating the symptoms associated with primary dysmenorrhea. Materials and Methods: A total of 60 participants in the age group of 18–26 years were recruited for the study and randomly divided into two groups. Pre-assessments (VAS and MSQ) were recorded on the 1st day of the menstrual cycle in both groups. Group 1 was given ginger tea for 3 weeks, once a day after dinner, from the 6th day of the menstrual cycle, while Group 2 was given cinnamon tea for the same duration. After the intervention, post-assessments (VAS and MSQ) will be recorded on the 1st day of the next menstrual cycle. All the details of the study were explained, and informed consent was obtained from the subjects. Results: In the present study, a paired sample t-test for within-group changes showed a significant reduction in VAS for pain (p≤0.05), SF (p≤0.05), MSQ (p≤0.05), and a significant increase in CF (p≤0.05) following ginger tea. A similar improvement in VAS for pain (p≤0.05), SF (p≤0.05), MSQ (p≤0.05), and a significant increase in CF (p≤0.05) were observed following cinnamon tea. Between-group changes performed using analysis of covariance for variables of interest adjusted for their respective baseline values indicated a significant difference in the visual analogue scale, CF, and SF; no significant changes were observed for MSQ. Conclusion: The study found that both ginger tea and cinnamon tea were effective in reducing menstrual pain and symptoms in primary dysmenorrhea subjects, with ginger tea being more effective than cinnamon tea.